Direct Femtosecond Laser Fabrication of Chemically Functionalized Ultra-Black Textures on Silicon for Sensing Applications - Borodaenko, Yulia (Nanomaterials (Basel), 2021)
Here, we present the single-step laser-assisted fabrication of anti-reflective hierarchical surface textures on silicon locally functionalized with a photoluminescent (PL) molecular nanolayer. Using femtosecond-laser ablation of commercial crystalline Si wafers placed under a layer of a solution containing rhodamine 6G (R6G) a triethoxysilyl derivative, we fabricated ordered arrays of microconical protrusions with self-organized nanoscale surface morphology. At the same time, the laser-induced temperature increase facilitated surface activation and local binding of the R6G derivative to the as-fabricated nanotextured surface. The produced dual-scale surface textures showed remarkable broadband (visible to near-IR) light-absorbing properties with an averaged reflectivity of around 1%, and the capping molecular nanolayer demonstrated a strongly enhanced PL yield. By performing a pH sensing test using the produced nanotextured substrate, we confirmed the retention of sensory properties of the molecules attached to the surface and validated the potential applicability of the high-performing liquid-assisted laser processing as a key technology for the development of innovative multifunctional sensing devices in which the textured substrate (e.g., ultra-black semiconductor) plays a dual role as a support and PL signal amplifier.